Jesuit colleges and universities in the United States a history - Rizzi, Michael T. (The Catholic University of America Press, 2022)
"Provides a comprehensive history of Jesuit higher education in the United States, weaving together the stories of the fifty-four colleges and universities that the Jesuits have operated (successfully and unsuccessfully) since 1789. It emphasizes the connections among the institutions, exploring how certain Jesuit schools like Georgetown University gave birth to others like Boston College by sharing faculty, financial resources, accreditation, and even presidents throughout their history. The book also explores how the colleges responded to common challenges-including anti-Catholic prejudice in the United States, the push from government authorities to modernize their shared curriculum, and the pull from Roman authorities to remain loyal to Catholic tradition. It covers themes like the rise of the research university in the 1880s, the administrative reforms of the 1960s, and the role of Jesuit colleges in racial justice, women's education, and other civil rights issues"--